Procurement of roller shutter for Masjid Kota Kemuning, Seksyen 31 Shah Alam / Mohammad Zulfazdley Mohd Zulkifli Cheng - Mohd Zulkifli Cheng, Mohammad Zulfazdley (Universiti Teknologi MARA, Perak, 2018)
Procurement is a crucial step in construction management, therefore this report will discuss about procurement, which is the process of obtaining goods and services from another after some considerations. This report was conducted for the construction of Masjid Kota Kemuning, Seksyen 31 Shah Alam. The objective of this report is to highlight the methods of procurement and to determine the problems occurred and solutions taken to overcome the issues. This report is carried out mainly using interviews, observations and documents reviewing methods. It focused on how the procurement is done, following each and every step from identifying the goods needed to purchasing stage, as well as the problem faced during the procedure. This report also looked at the efficiency management based on time, quality and cost that can be used to lessen problems and delays in construction process, and also as a reference document. As conclusion, procurement is seen as an important process as it helps ensuring continuity and consistency during construction process.